A tryptophan metabolite made by a gut microbiome eukaryote induces pro-inflammatory T cells - Wojciech, Lukasz; Png, Chin Wen; Koh, Eileen Y; Kioh, Dorinda Yan Qin; Deng, Lei; Wang, Ziteng; Wu, Liang Zhe; Hamidinia, Maryam; Tung, Desmond Wh; Zhang, Wei; Pettersson, Sven *; Chan, Eric Chun Yong; et al. (EMBO Press, 2023)
The large intestine harbors microorganisms playing unique roles in host physiology. The beneficial or detrimental outcome of host-microbiome coexistence depends largely on the balance between regulators and responder intestinal CD4+ T cells. We found that ulcerative colitis-like changes in the large intestine after infection with the protist Blastocystis ST7 in a mouse model are associated with reduction of anti-inflammatory Treg cells and simultaneous expansion of pro-inflammatory Th17 responders. These alterations in CD4+ T cells depended on the tryptophan metabolite indole-3-acetaldehyde (I3AA) produced by this single-cell eukaryote. I3AA reduced the Treg subset in vivo and iTreg development in vitro by modifying their sensing of TGFβ, concomitantly affecting recognition of self-flora antigens by conventional CD4+ T cells. Parasite-derived I3AA also induces over-exuberant TCR signaling, manifested by increased CD69 expression and downregulation of co-inhibitor PD-1. We have thus identified a new mechanism dictating CD4+ fate decisions. The findings thus shine a new light on the ability of the protist microbiome and tryptophan metabolites, derived from them or other sources, to modulate the adaptive immune compartment, particularly in the context of gut inflammatory disorders.